Misconception Profile on Photosynthesis by Using Four-Tier Diagnostic Test on Twelve Grade Students of Senior High School - Nadya Eka Aristyasari; Yuliani Yuliani (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2021)
Misconception is a concept that is incompatible with scientific understanding or with experts in the field. If misconceptions are not immediately resolved, they will continue to be stored in the students' memory, it will have a negative impact on concept acceptance and understanding of the next material because concepts in biology are interrelated. Photosynthetic sub-material is one of the materials in Biology where misconceptions are often found. This concept is a complex and abstract so that students have difficulty to understanding it. The purpose of this research is to describe the profile of students' misconceptions in the photosynthesis submission by using four-tier diagnostic test. This research is a descriptive evaluative research, was make four-tier diagnostic test instrument that is validated by two expert, testing questions, analyzing the results of the research by using category tables and criteria for the level of misconceptions, and make a conclusions. The subjects in this study were 60 students of class XII who had received photosynthesis material. The data obtained were analyzed using a table of students' conception criteria based on four-tier test. The results showed that the profile of students' misconceptions consisted of students who experienced misconceptions which was 45.5%, students who understood the concept was 28%, and students who did not understand the concepts was 26.5%. The criteria for the level of misconception among students were high misconception was 46.7%, moderate misconception was 29.8%, and low misconception was 23.5%. Keywords: profile, misconception, photosynthesis, four-tier diagnostic test.